2012
DOI: 10.1037/a0026224
|View full text |Cite
|
Sign up to set email alerts
|

How learning about scientists' struggles influences students' interest and learning in physics.

Abstract: How does leaming about scientists' stmggles during their scientific knowledge building affect students' science leaming? Two hundred and seventy-one high school students were randomly assigned to 1 of 3 conditions: (a) the struggle-oriented background information (n = 90) condition, which presented students with stories about 3 scientists' stmggles in creating the content knowledge that the students were leaming through online physics instructional units; (b) the achievement-oriented background information (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 89 publications
6
120
0
3
Order By: Relevance
“…Research has shown that underdog stories have a positive impact on hope and motivation, and may therefore facilitate motivation and goal pursuit in general (e.g. Hong & Lin-Siegler, 2012;Prestin, 2013). Examining the consequences of being moved on behaviour would be another fruitful direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that underdog stories have a positive impact on hope and motivation, and may therefore facilitate motivation and goal pursuit in general (e.g. Hong & Lin-Siegler, 2012;Prestin, 2013). Examining the consequences of being moved on behaviour would be another fruitful direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…History of physics: has a great potential for the formation of learnersí motivation to study physics (Rowcliffe, 2004;Eshach, 2009;Hong & Lin-Siegler, 2012). The elucidation of the contribution of physicists to science would cultivate the respect to the profession of scientists (Korsun, 2017a).…”
Section: Figure 2 Active Means Of Training For the Formation Of Learmentioning
confidence: 99%
“…That's why the students tend to use printed media as learning resource. Allen (Daryanto, 2010: 18) clustering teaching research into nine that were visual, film, television, 3D object, recording, lesson programed, demonstration, spoken presentation, and printed media (Hong and Lin-Siegler, 2011). Printed media can be newspaper, magazine, supplement book, lesson book and also encyclopedia.…”
Section: Introductionmentioning
confidence: 99%